Quality and singularitas. For a metaphysics of the body - Malaguti, Ilaria (Scenari, 2021)
The article reads the moments of birth and death as events of embodiment of the sense. The body itself, in this perspective, stands out as an event that breaks the order of the world: each individual is an horizon of meaning that interacts with the reality it a singular, specific way. Following the path of Rosenzweig and Merleau-Ponty, the Author describes the proximity of body and world as parentage retraceable in the Bible. This relationship between flesh and earth is not a mere bond of blood, but it expresses what Henry interprets on the basis of the notion of incarnation. The essay, then, analyzes Biran’s corps propre and transcendental body, highlighting that non-intentional phenomenology can develop the theme of corporeality as original passivity and transcendental internal experience. The theological category of incarnation, thus, belongs also to the philosophical debate: the flesh defines a truly human way of being that surpasses any materialistic or biological interpretation. The resurrection, therefore, becomes part of the revelation as well as a phenomenological category, as Marion underlines. Revelation is the principle by which quality becomes a guiding criterion of the manifestation through the flesh and the way by which a singularity can express itself. In conclusion, the body is defined as ark that preserves and witnesses an invisible and not immediately sensible presence.